Alcohol Ban and Crime: The ABCs of the Bihar Prohibition - Chaudhuri, Kalyani; Jha, Natasha; Nilayamgode, Mrithyunjayan; Suryanarayana, Revathy (Economic Development and Cultural Change, 2024)
We study the relationship between alcohol consumption and crime after an alcohol prohibition in Bihar, India, in 2016. Using a difference-in-differences approach, we explore the differential effects of alcohol on different crime types. We find that the prohibition led to a 0.22 standard deviation point reduction in reported violent crimes without significantly affecting nonviolent crimes. Heterogeneity tests reveal stronger effects in interior districts and in districts with higher baseline alcohol consumption or fewer religious restrictions on alcohol consumption. Thus, we conclude that the ban affected crime by reducing alcohol availability and consumption rather than through institutional changes.
Keywords: Alcohol Availability; Alcohol Ban; Alcohol Consumption; Bihar Prohibition; Crime; Heterogeneity